2023
DOI: 10.1590/1678-4499.20220177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar as a hydroponic substrate on growth, colour and nutritional content of red lettuce (Lactuca sativa L.)

Abstract: Hydroponic is a technique of growing plants in a soilless medium by using a sponge, rock wool, hydroton, coconut coir, and perlite as an alternative for crop production systems. Recently, biochar has been reported to be a potential substrate for hydroponic cultivation techniques due to its physicochemical properties which can help increase vegetable production. A greenhouse study was conducted to investigate the effect of biochar as hydroponic substrate on the growth, colour and nutritional content of red lett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Conversely, the lowest amounts of leaf chlorophyll content were observed in the M 0 N 1 treatment for palak (21.46 mg/g). These results align with the findings of Rosli et al (2023), who assessed the impact of potassium on tomatoes and reported that increased potassium content led to a noticeable decrease in chlorophyll content. Additionally, Thakur et al (2019) supported these findings, emphasizing the positive correlation between increased photosynthesis and higher yields.…”
Section: Figuresupporting
confidence: 91%
“…Conversely, the lowest amounts of leaf chlorophyll content were observed in the M 0 N 1 treatment for palak (21.46 mg/g). These results align with the findings of Rosli et al (2023), who assessed the impact of potassium on tomatoes and reported that increased potassium content led to a noticeable decrease in chlorophyll content. Additionally, Thakur et al (2019) supported these findings, emphasizing the positive correlation between increased photosynthesis and higher yields.…”
Section: Figuresupporting
confidence: 91%